2017
DOI: 10.1093/jee/tox126
|View full text |Cite
|
Sign up to set email alerts
|

The Role of p38 MAPK, JNK, and ERK in Antibacterial Responses of Chilo suppressalis (Lepidoptera: Crambidae)

Abstract: The mitogen-activated protein kinases (MAPKs) are conserved signal transduction pathways and broadly responsible for bacterial infection from yeast to mammals, and virus, fungi, and bacteria, specifically Bacillus thuringiensis, to insects. But little is known about the MAPK pathways in antibacterial responses in Chilo suppressalis (Walker), an important lepidopteran pest of rice. In this study, we used the bacteria of Bacillus thuringiensis, Escherichia coli, and Staphyloccocus aureus to infect C. suppressali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Numerous studies have shown that the MAPKs such as ERK1/2 are activated upon stimulation of cells, including pathogenic infection [40][41][42]. In this context, to further investigate the possible mechanisms underlying the antiinflammation effects of BV, phosphorylation of ERK1/2 was determined in cells exposed to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that the MAPKs such as ERK1/2 are activated upon stimulation of cells, including pathogenic infection [40][41][42]. In this context, to further investigate the possible mechanisms underlying the antiinflammation effects of BV, phosphorylation of ERK1/2 was determined in cells exposed to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, results from both in vivo and in vitro investigations showed that DOX exposure suppressed the nuclear translocation of Nrf2. A set of protein kinases referred as MAPKs were believed to regulate the activation of Nrf2/ARE signaling [ 28 ]. MAPKs including JNK, ERK1/2, and p38MAPK were reported involved in cellular defense responses to stressful factors such as ROS [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In M. sexta and Aedes aegypti, Cry toxin intoxication activates the p38 MAPK pathway, and the knockdown expression of p38 MAPK leads to an increased sensitivity to Bt Cry toxin (Cancino-Rodezno et al, 2010). Similarly, when the p38 MAPK pathway is silenced via RNAi, the susceptibility of C. suppressalis larvae to the Bt Cry1Ca toxin is significantly increased (Qiu, Fan, et al, 2017). Our results showed that Bt Cry1Ab activated OfERK expression at the transcriptional level at 24, 48, and 72 h posttreatment.…”
Section: The Regulation Of Oferk On Immune- Developmental-and Stress-...mentioning
confidence: 56%
“…It also showed that Cry1Ab toxin significantly induced OfERK expression, and the phylogenetic analysis revealed that OfERK has the closest homolog with Cs‐ERK2 from C. suppressalis . It has been reported that Cs‐ERK 2 is involved in response to Bt infection (Qiu, Zhang, et al, 2017). Therefore, we postulated that OfERK has a potential function in defense against Bt infection.…”
Section: Discussionmentioning
confidence: 99%